A Whole Different Ballgame: Comparing the CSR Activities of the English Premier League and the National Football League in Response to the 2020 BLM Protests - von Ebbe, Isabella Maria (2020)
Corporate social responsibility (CSR) can be ambiguous in definition. Thus, it is valuable to investigate the concept in different contexts to shed light on the successes and pitfalls of various approaches. This dissertation’s research question asked, “How did the English Premier League (EPL) and the National Football League (NFL) react in terms of CSR activities to the 2020 Black Lives Matter (BLM) protests?” The objectives were to identify the leagues’ stakeholders and their pressures, examine the drivers and challenges, and critically evaluate the responses through a comparative international lens. The research methods consisted of content analyses run on various secondary sources. League actions and statements pertaining to the BLM movement were crucial qualitative data. Constructed with the findings were timelines of the main events and stakeholder mappings utilized to compare pressures. In terms of programs initiated in response to the movement, the EPL created an online racist abuse reporting system and a minority player-to-coach placement scheme. The NFL launched a voter engagement initiative for the 2020 US presidential election. Improving reputation, maintaining legitimacy, and managing stakeholders drove the organizations to make immediate responses and present clear action plans. Additionally, the differing levels of state involvement propelled the American league to employ political CSR, whereas the English league remained apolitical. Ultimately, the study found that the EPL engaged proactively and the NFL engaged reactively. From this dissertation, it is recommended that organizations’ CSR responses to social movements should be proactive, consult stakeholders, and prioritize moral obligations over political or financial objectives.